Use of system approach for studying of the ecological situation of the city green space (on the example of «Chernyaevsky forest» of Perm) (Eurasian Journal of Ecology, 2016)
Article contains results of researches of an ecological situation of the green space of the city on the basis of system methodology. The scheme which reflects ideas of structure and features of functioning of the systempossessing high degree of complexity is as a result created. The object of research is “Chernyaevsky forest” in Perm. The contribution of technogenic, abiotic and biotic factors to formation of forest-park landscapesis considered. As result – territory zoning on intensity of an ecological situation.
Keywords: system approach; ecological situation; structurally functional scheme; territory zoning